Analisis Pengendalian dan Pencegahan Penyakit Infeksi Berbasis Kesehatan Lingkungan Dalam Era Pandemi Covid-19 di Puskesmas Kabupaten X Tahun 2021 - Luthfil Hadi Anshari; Ch. Tuty Ernawati; Ulfah Winanda Putri (STIKes Hang Tuah Pekanbaru, 2022)
Efforts to prevent and limit the transmission of infection in health centers during the Covid-19 pandemic are important because of the many activities of health centers conducting swab tests, vaccination activities and other service activities that cause the transmission of infection. This study aimed to find out the picture of control and prevention of infectious diseases based on environmental health in the health center of district X. This study was a mixed method study with the determination of qualitative research informan and purposive sampling and the sample of study was 75 respondents.The results showed that there was a lack of knowledge level of the health workers. Input: there were policies such as SOPs, HR PPI teams consisting of doctors, nurses, and sanitation workers, infrastructure facilities are available and funds come from BLUD. Process: the implementation of hand hygiene, PPE, waste management, environmental control has been implemented, and some are not in accordance with regulations such as sorting waste that is still mixed, transporting waste that is late and also waste storage that has not used coldstorage, Output: the management of medical waste puskesmas has been implemented and has not been in accordance with applicable regulations. The conclusion of medical waste management has not been in accordance with Decree No. 27/2017 and Permen LHK No. 56/2015. Suggestions to coordinates and cooperates with cross-sector related sectors in addressing medical waste problems and improving environmental health-based infection disease control and prevention efforts.